Review article Approach and management of chronic hiccups- a common but difficult entity : Approach and management of chronic hiccups- a common but difficult entity (Bombay Hospital Journal, 2026)
Hiccups are quite common and often troublesome for patients and even for physicians as approach and management are not thoroughly clear. This review discusses about hiccups from epidemiology, classification, etiologies, mechanism involved, approach to patient, home remedies to pharmacological drugs to tackle the hiccups. In majority of cases underlying pathology is quite not clear when patient presents with hiccups of more than 48 hours duration. It is advisable to start proton pump inhibitors as initial drug of choice as gastroesophageal reflux diseases are found to be most common underlying etiology for hiccups. Treatment should be changed or combination therapy should be initiated if patient is not responding to first line agent after 1-2 weeks. Weightage should be given to associated symptoms with hiccups as they guide to pathology There is a lack of strong evidence based pharmacological and surgical data that suggests an effective step wise solution to this common problem. Large patient-controlled trials are necessary for alternative therapies like acupuncture and hypnosis to place them in proper management plan with enough evidence.